ANALISA PENGARUH BRAND CREDIBILITY DAN PERCEIVED QUALITY TERHADAP PURCHASE INTENTION DENGAN CUSTOMER BEHAVIOUR TOWARDS CO-BRANDING STRATEGY SEBAGAI VARIABEL MEDIASI PRODUK KARTU DEBET CO-BRANDING BNI-CHELSEA FC - Roy Saputra Setiawan (Jurnal Strategi Pemasaran, 2015)
This research aims to analyze the influence of Brand Credibility and Perceived Quality Towards Purchase Intention in co-branded product BNI-Chelsea debit card through consideration of Customer Behaviour Toward Co-branding Strategy. The sample in this study amounted to 100 respondents are people who are fans of Chelsea and BNI debit card users. The sampling technique in this study using purposive sampling technique. Type of collecting data in this study using questionnaires to sample of research. The research proves Customer Behaviour Toward Co-Branding Strategy and Perceived Quality has a direct influence on Purchase Intention, but only Brand Credibility that do not directly affect on Purchase Intention